Factors Affecting Food Prices in Pakistan (The Pakistan Development Review, 2025)
The purpose of the study is to identify the factors affecting food prices in Pakistan. The findings reveal that there is a negative and significant impact of the real effective exchange rate on wheat prices in the long run. Similarly, the real interest rate affects wheat and rice prices indirectly, while it has a direct impact on tea prices. There is a positive and significant impact of international crude oil prices and international food prices on most food commodities. Moreover, the study explains that in the long run, the increase in local production significantly reduces the prices of food commodities. It is also found that the government policy of adjusting (increasing) wheat support prices also has a positive and significant impact on wheat prices.